Miskonsepsi siswa dalam menyelesaikan soal ceritaPada materi lingkaran(studi situs di kelas viii g semester genap mts negeri ngemplak boyolali) - Suaebah, Elvilia; , Masduki, S.Si, M.Si (2016)
The purpose of this study to describe misconceptions and the cause of misconceptions to the subject eighth grade students of MTs Negeri Ngemplak in story problems on the circle. This research used descriptive qualitative method. Data collection techniques by observation, tests and interviews. Data validity checking with the technique of triangulation method, by comparing the results of tests, interviews and observations. Analysis of the data through the stages of data reduction, data Data Display, and conclusion. Based on data analysis and discussion concluded students' misconceptions seen from: 1. Understanding the problem, misconceptions in defining the language, interpret images and create mathematical models, the cause of the misconception is reasoning incomplete / incorrect and ability of the students.2. Devising a plan, misconceptions about linking relationships concepts, the cause of the misconception is humanistic thinking 3. Carry out plan, misconceptions about the use of the formula is incorrect and use the wrong unit, the cause of the misconception is reasoning incomplete / incorrect and humanistic thinking